Fernando da Rocha Peres: poesia e cidade – diálogos com a modernidade - Araújo, Rafaela Giovana Lima Santana de (2012)
This dissertation presents an analytical reading of the representations of modernity in selected poems by the poet Fernando da Rocha Peres (1936- ), having as research corpus the books Febre Terçã (2000) and Salvadolores ou Coisas de Amor (2004). The study was accomplished through bibliographical investigation and literary analysis, observing events and themes recurring in his lyrical production. In order to do so, the aspects considered were: metalanguage, time passing and the city. Before the critical appreciation, a contextualization of the modern scenario was made and then, the contemporary poetical production was reached, and specifically, the production of the author in question. The definition of the poetic profile of this author was considered relevant, having as basis the dialog established with tradition and Modernity through representative authors of Western literature, the historical elements of the discourse and the lyrical subjectivity before contemporaneity.